2008
DOI: 10.1021/jp8078293
|View full text |Cite
|
Sign up to set email alerts
|

Products and Kinetics of the Liquid-Phase Reaction of Glyoxal Catalyzed by Ammonium Ions (NH4+)

Abstract: Glyoxal, a common atmospheric gas, has been reported to be depleted in some regions of the atmosphere. The corresponding sink could be accounted for by reactions in or at the surface of atmospheric particles, but these reactions were not identified. Recently, we showed that inorganic ammonium ions, NH(4)(+), are efficient catalysts for reactions of carbonyl compounds, including glyoxal, in the liquid phase. To determine whether ammonium-catalyzed reactions can contribute to depletion of glyoxal in the atmosphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
394
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 276 publications
(425 citation statements)
references
References 22 publications
28
394
2
1
Order By: Relevance
“…oxalate, oligomers, organosulfate and imidazole). [6,8,[32][33][34] Because these compounds are found predominantly in the condensed phase in the atmosphere, aqueous reaction of GLY contributes to SOA aq . [32,33] Organic nitrogen and sulfur compounds have been observed to form in highly concentrated aqueous solutions relevant to wet aerosols.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…oxalate, oligomers, organosulfate and imidazole). [6,8,[32][33][34] Because these compounds are found predominantly in the condensed phase in the atmosphere, aqueous reaction of GLY contributes to SOA aq . [32,33] Organic nitrogen and sulfur compounds have been observed to form in highly concentrated aqueous solutions relevant to wet aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…[32,33] Organic nitrogen and sulfur compounds have been observed to form in highly concentrated aqueous solutions relevant to wet aerosols. [6,[34][35][36][37] Evidence for the photochemical formation of organosulfates from GLY and other aldehydes is provided through studies of bulk sulfate solutions and through smog chamber experiments with ammonium sulfate seed particles and UV irradiation. [6,35,36] Aerosol mimic solutions containing GLY and inorganic ammonium salts have yielded products with carbon-nitrogen bonds in the absence of major atmospheric oxidants (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may exist branching points in these reactions, favoring one type of chromophore over another according to the acidity. Noziere et al (2009) observed that the iminium ion pathway, incorporating N, is faster at higher pH while the traditional aldol condensation is favored at lower pH. This suggests that the incorporation of N-containing products has a pH dependence as well.…”
Section: Introductionmentioning
confidence: 96%
“…In most cases, it was concluded that chromophores form fastest in basic solution, because nitrogen (in ammonia, methylamine, or amino acids) must initiate a nucleophilic attack at the carbonyl carbon atom (Yu et al, 2011;Kampf et al, 2012). However, several studies have shown that aldol condensation of dicarbonyls can be acid catalyzed (Noziere et al, 2009) and that aldol condensation products may contribute to visible light absorption (Sareen et al, 2010). This leaves the relationship between pH and absorptivity in amine-aldehyde reactions unclear.…”
Section: Introductionmentioning
confidence: 99%